INFLUENCE OF READING WHILE LISTENING (RWL) IN IMPROVING LISTENING COMPREHENSION AND VOCABULARY RETENTION AMONG GRADE 10 STUDENTS - T. Calma , Princess (LP2M Universitas Bina Mandiri Gorontalo, 2023)
Language learning has significant key variables that effectively aids the students to learn easier. Language learning has significant key variables that effectively aids the students to learn easier. When language learners listen to a language, multiple challenges come up. With this the researchers suggested the Reading while Listening approach in order to improve the students listening comprehension and vocabulary retention. This study used the quantitative method of research among the Grade 10 students enrolled in Pagalanggang National High School. Under the quantitative research, the proponents of this study employed experimental research design since the researcher will measure how reading while listening can influence the improvement of listening comprehension and vocabulary retention of students.In this case, the proponents of this study utilized researchers-made instrument wherein the researcher designed six (6) sets of semi-detailed lesson plan. All lesson plans were all based on K-12 English Curriculum. Also, pretest and posttest were constructed by the Researchers aligned with the semi-detailed lesson plan. Two groups from Grade 10 students’ results were compared: (1) using the Reading while Listening approach, and the other (2) using the Traditional Approach where the teacher will be the one who reads in front of the class. As a result, RWL has a significant impact on the performance of the students in terms of listening comprehension. The Mean Percentage Score of the experimental group jumped from 40.33 to 75.2, unlike the control group’s MPS from 42.77 to 62.67, which obviously shows the gap between the two.